Fruit, vegetable, and fruit juice consumption and risk of gestational diabetes mellitus: a systematic review and meta-analysis - Yan-Ping Liao; Qing-Xiang Zheng; Xiu-Min Jiang; Xiao-Qian Chen; Xiao-Xia Gao; Yu-Qing Pan (Nutrition Journal, 2023)
Abstract Background Fruit, vegetable, and fruit juice intake is associated with the risk of gestational diabetes mellitus (GDM). However, the conclusion is limited and conflicted. The purpose of this systematic review and meta-analysis is to investigate the association between fruit, vegetable, and fruit juice consumption and the risk of GDM. Methods To find relevant studies, we searched PubMed, The Cochrane Library, Web of Science, Embase, ScienceDirect, PsycINFO, CINAHL, Ovid, EBSCO, CBM, CNKI, Wanfang Data, and VIP for the report on prospective cohort studies published from inception to April 8, 2022. Summary relative risks (RR) and 95% confidence intervals (Cis) were estimated using a random-effects model. Results A total of 12 studies with 32,794 participants were included in the meta-analysis. Total fruit consumption was associated with a lower risk of GDM (RR = 0.92, 95% CI = 0.86–0.99). Whereas an increasing the consumption of vegetable, including all vegetable (RR = 0.95, 95% CI = 0.87–1.03), starchy vegetable (RR = 1.01, 95% CI = 0.82–1.26), and fruit juice (RR = 0.97, 95% CI = 0.91–1.04) was not associated with a reduction in the risk of GDM. In a dose‒response analysis of eight studies, a 3% reduction in risk of GDM for a 100 g/d increase in fruit consumption (RR = 0.97, 95% CI = 0.96–0.99). Conclusions The findings suggest that higher fruit consumption may reduce the risk of GDM, with a 3% reduction in the risk of GDM for every 100 g/d increase in fruit intake. Higher-quality prospective studies or randomized clinical trials are required to validate the effect of different variations of fruits, vegetables, and fruit juice consumption on the risk of GDM.